2015
DOI: 10.1007/978-3-319-17398-6_22
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of 2D UMI and 3D Zernike Shape Descriptor for ATS Drugs Identification

Abstract: Drug abuse is a threat to national development. Generally, drugs can be identified based on the structure of its molecular components. This procedure is becoming more unreliable with the introduction of new amphetamine-type stimulants (ATS) molecular structures which are increasingly complex and sophisticated. An in-depth study is crucial to accurately identify the unique characteristics of molecular structure in ATS drug. Therefore, this chapter is meant for exploring the usage of shape descriptors (SD) to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…On the other hand, the features are tested in terms of classification accuracy against well-known classifier, Random Forest (RF) [77] from WEKA Machine Learning package [78]. RF is employed in this study, because previous studies conducted by [51], [79]- [81] have found that RF is the most suitable for the molecular structure data. In this study, the number of trees employed by RF is 165, equals to the number of attributes of all 3D moments.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the features are tested in terms of classification accuracy against well-known classifier, Random Forest (RF) [77] from WEKA Machine Learning package [78]. RF is employed in this study, because previous studies conducted by [51], [79]- [81] have found that RF is the most suitable for the molecular structure data. In this study, the number of trees employed by RF is 165, equals to the number of attributes of all 3D moments.…”
Section: Methodsmentioning
confidence: 99%
“…The 3D Zernike descriptors have been successfully applied to protein structural similarity retrieval ( Mak et al, 2008 ; Sael et al, 2008 ), protein-protein docking using region-based ( Venkatraman et al, 2009b ), terrain matching ( Ye and Chen, 2012 ), and amphetamine-type stimulant (ATS) drugs identification ( Pratama et al, 2015 ). The maximum order of 3D Zernike moments used in most, if not all, studies is below 30 and can only represent the rough shape features of 3D objects because the existing computation method developed by Novotni and Klein is time-consuming and computationally instable for calculating higher orders of Zernike moments ( Zhang et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%